Mapping the global research landscape on psoriasis and the gut microbiota: visualization and bibliometric analysis - Zou, Yue-Min; Wu, Man-Ning; Zhou, Xiangnan; Bai, Yan-Ping (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundPsoriasis is a common chronic inflammatory skin disease with a complex pathogenesis. Recently, the role of gut microbiota in psoriasis has attracted increasing attention. A systematic bibliometric analysis of relevant literature is necessary to understand better the current state and development trends in this field.Materials and methodsThe Web of Science Core Collection database was searched for literature indexed from 2004 to October 15, 2024. Bibliometric analysis was conducted using Bibliometrix, CiteSpace (version 6.3.R1), R 4.2.2 with the Bibliometrix package, Scimago Graphica 1.0.45, and VOSviewer (version 1.6.20.0) to visualize publication types, years, authors, countries, institutions, journal sources, references, and keywords.ResultsThe development of psoriasis and gut microbiota research can be divided into two phases: slow growth (2004–2014) and rapid development (2014–2024). Lidia Rudnicka is the most active and influential author. China produced the highest number of publications, followed by the United States, which had the highest number of citations per article. The International Journal of Molecular Sciences published the most articles. In contrast, articles in the Journal of Investigative Dermatology, British Journal of Dermatology, and Journal of Allergy and Clinical Immunology were cited over 1,000 times. Keyword and co-citation analyses identified evolving research hotspots. Early studies focused on the association between gut microbiota and comorbid inflammatory diseases. Recent research has delved into specific mechanisms, such as disruption of gut barrier function, short-chain fatty acid metabolism alterations, impaired regulatory T-cell function, and excessive activation of Th17 cells. These mechanisms highlight how gut dysbiosis exacerbates psoriasis patients’ systemic inflammation and skin lesions.ConclusionThe field of psoriasis and gut microbiota research is developing rapidly despite uneven research distribution. This bibliometric evaluation assesses the current state of research and provides new perspectives for understanding the complex interactions between microbes and the host. Future efforts should strengthen international collaboration to deeply explore the mechanisms of gut microbiota’s role in psoriasis, especially its potential applications in disease diagnosis and treatment.